Podejście procesowe w komunikacji wewnętrznej przedsiębiorstwa - Bednarz, Krzysztof Kazimierz (A Process Approach in the Internal Communication of Business, 2009)
A process approach in the internal communication of business is nowadays one of the most important factors of the firm's development in the age of information society. The issue of internal movements inside of an organization and movements through the territory of the whole world does not have recently a significant meaning in accomplishment of strategic target (goal) of a firm. As far as organization, work and performance are concerned, more important is an efficient organization of communication between each department of a firm as well as the one with the external world. The author in his article according to his own research tries to describe a process of internal communication and additionally indicates the new directions of its extension. To enable particular firms to develop, necessary changes are requested as far as communication and sharing of knowledge are concerned. The co-operation with the internal environment and sharing/exchanging of knowledge is essential for evolution, growing and spread of innovations and advancement of communication processes in the near future. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 52, s. 23-33